2018
DOI: 10.1002/ece3.4061
|View full text |Cite
|
Sign up to set email alerts
|

Simple foraging rules in competitive environments can generate socially structured populations

Abstract: Social vertebrates commonly form foraging groups whose members repeatedly interact with one another and are often genetically related. Many species also exhibit within‐population specializations, which can range from preferences to forage in particular areas through to specializing on the type of prey they catch. However, within‐population structure in foraging groups, behavioral homogeneity in foraging behavior, and relatedness could be outcomes of behavioral interactions rather than underlying drivers. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 75 publications
0
30
0
Order By: Relevance
“…Many studies suggest that non-random structural features of social networks, such as multi-level or hierarchical structures or phenotypic assortativity, represent the outcome of complex behaviours. However, many passive processes or simple mechanisms can also impose non-random patterns in social structure (Cantor et al 2012;Mourier et al 2012;Firth et al 2017;Cantor and Farine 2018), which can strongly affect a range of population-level processes spanning both ecology and evolution. Environmental factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggest that non-random structural features of social networks, such as multi-level or hierarchical structures or phenotypic assortativity, represent the outcome of complex behaviours. However, many passive processes or simple mechanisms can also impose non-random patterns in social structure (Cantor et al 2012;Mourier et al 2012;Firth et al 2017;Cantor and Farine 2018), which can strongly affect a range of population-level processes spanning both ecology and evolution. Environmental factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Cantor and Farine 35 demonstrated, using agent-based models, that simple foraging interactions in competitive environments may give rise to the formation of stable social groups consisting of relatives. They showed that a process by which 'individuals keep foraging with the same individuals if they were successful together in the past' can lead to a stable social community structure and the emergence of kin-structure via fitness benefits or philopatry 35 . Their models, based on an energetic reward (food), provides an alternative evolutionary mechanism for the formation of stable, kin-based social groups similar to those observed in many vertebrates 35 .…”
mentioning
confidence: 99%
“…These studies have been mostly descriptive (with some prominent exceptions such as the model of Seyfarth 10 ), but a new generation of studies are trying to explain observed patterns using generative models 11,12,13,14 . In one of these studies, Ilany and Akçay recently proposed social inheritance, defined as a tendency of offspring social affiliations to resemble those of their parents, as a general process that can explain the structure of social networks of multiple species 12 .…”
Section: Introductionmentioning
confidence: 99%